Amrubicin: potential in combination with cisplatin or carboplatin to treat small-cell lung cancer - Ding Q; Zhan J (Dove Medical Press, 2013)
Qian Ding, Jinbiao ZhanDepartment of Biochemistry, Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaAbstract: Small-cell lung cancer (SCLC) is the most aggressive form of lung cancer characterized by early metastasis and high mortality. In recent years, monotherapy and combination therapy of amrubicin with cisplatin or carboplatin has been actively studied and shown promise for the treatment of extensive disease SCLC (ED-SCLC). In this article, we summarize clinical trials of both monotherapy and combination therapy with amrubicin conducted in Japan, the USA, and the European Union. The results suggest that the clinical outcome of amrubicin therapy may be associated with genetic variations in patients. Further study of combination regimens in patients of different ethnicities is warranted.Keywords: amrubicin, cisplatin, carboplatin, combination therapy, small-cell lung cancer, antibody-drug conjugates